Modeling spatial and temporal variability in a Folsom lithic scatter: views from the Reddin site, San Luis Valley, Colorado - Meyer, Kelton A., author; LaBelle, Jason M., advisor; Pante, Michael C., committee member; Van Buren, Mary, committee member; Shaby, Ben A., committee member (Colorado State University. Libraries, 2025)
This dissertation explores Folsom mobility and campsite organization through the analysis of the Reddin site (5SH77), San Luis Valley, southern Colorado. Current models of Folsom mobility in the region focus on sites with buried and spatially discrete components, often representing single occupation events associated with bison hunting, lithic procurement, seasonal aggregation, or a combination of these activities. Reddin is a surface scatter of lithic debris lacking a buried horizon, but it includes a large Folsom assemblage and exhibits evidence of multiple occupations. Lithic analysis suggests Reddin was a place used for residential downtime and retooling broken equipment. I applied spatial statistical methods to detect multiple Folsom camps at the site using artifacts commonly associated with residential areas. Reddin contains at least 14 Folsom camps averaging more than 160 m distant, each with variable artifact densities. I then explored Folsom mobility patterns in each cluster by calculating mean per capita occupation span, based on artifact accumulation over time. I developed a new method of calculating occupation span using the steady accumulation of burned lithic debris, a common attribute of Folsom campsite spaces. The results indicate that each campsite was used for different lengths of time, representing a spectrum of Folsom mobility strategies used in the Valley's center. Multiple Folsom occupations at Reddin suggest the formation of a local cultural geography, which likely evolved in complexity with sequential visits to the site. Unless otherwise noted, all data, tables, maps, and figures in this dissertation were produced by the author.
Keywords: hunter-gatherer; Rocky Mountains; spatial; lithics; Folsom; southwest